2005
DOI: 10.1007/s10453-005-9004-9
|View full text |Cite
|
Sign up to set email alerts
|

Using selective media to assess aerosolization damage and ultraviolet germicidal irradiation susceptibility of Serratia marcescens

Abstract: This study determined whether selective media, McConkey agar (MC) and minimal salt glucose agar (MA) are suitable for monitoring aerosolization damage of airborne Serratia marcescens in our laboratory aerosol exposure system and assessed the relationship between bacterial culturability in these media and ultraviolet germicidal irradiation (UVGI) susceptibility of the bacteria. Two types of bacterial cultures were prepared. The first culture was taken from bacteria growing on Tryptic soy agar (TSA) as complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The result demonstrated that VUV light could be an effective measure for chemical degradation in ventilation systems. When it comes to disinfection, extensive research has been carried out on UVC light and effective destruction of both airborne [8][9][10][11][12][13][14][15][16][17][18][19][20] and other human pathogens [21][22][23][24][25][26][27][28][29] has been shown. Nevertheless, disinfection using VUV light has attracted very little attention.…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrated that VUV light could be an effective measure for chemical degradation in ventilation systems. When it comes to disinfection, extensive research has been carried out on UVC light and effective destruction of both airborne [8][9][10][11][12][13][14][15][16][17][18][19][20] and other human pathogens [21][22][23][24][25][26][27][28][29] has been shown. Nevertheless, disinfection using VUV light has attracted very little attention.…”
Section: Introductionmentioning
confidence: 99%